Pengembangan Aplikasi Mobile Learning Bahasa Jawa (JawApp) berbasis Android dengan Metode Prototyping - Moh. Faiz Fanani; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Mobile learning is now widely used as an alternative medium to support teaching and learning in schools. One of them is learning Javanese at the junior high school level. As in one of the schools sampled in this study is SMPN 3 Malang. From previous interviews, with Ms. Fita Mayasari as a regional language teacher at SMPN 3 Malang, it was concluded that from the many alternative learning media that have been used, there are still some redundant features and are not in line with the needs of supporting teaching and learning in SMPN 3 Malang. Therefore, it is necessary to make an alternative learning media application that is suitable to the needs during the learning process, especially learning Javanese. Application made based on Android. This is because the majority of smartphone users in Indonesia are users of devices with the Android operating system. The application development process is carried out with a prototyping method approach in order to produce a valid product in accordance with stakeholder needs. From the results of the tests conducted, it was found that functional testing results on 14 requirements were declared valid. Then in terms of usability with the USE questionnaire method, the results obtained in all aspects above 71% so that it was declared feasible. In addition, the results of the compatibility of the application also work well on Android devices starting from version 5.0 (Lollipop) to version 9.0 (Pie).